2019
DOI: 10.1002/pa.2004
|View full text |Cite
|
Sign up to set email alerts
|

Social media taxation and its impact on Africa's economic growth

Abstract: Technology affordances enable citizens to digitally connect and collectively act towards realization of established economic goals of a given country. This paper contributes to scholarly discussions on the effects of social media tax on Africa's economic growth. For African economies to grow, there is need to abolish social media tax and device means through which social media discussions that generate billions of data are captured and analyzed to guide policymaking processes aimed at economic growth. We conno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Furthermore, a study conducted by (Angelopoulos et al, 2007;Kate and Milionis, 2019) mostly contradicts previous studies on the negative effect of corporate income tax on the economy such as (Arnold et al, 2011) contend; higher corporation taxes may encourage private innovative activities and help produce funds for beneficial public investment and may promote growth while simultaneously introducing for the state some cutting edge technologies. The relationship between corporate tax rates and growth, on the other hand, may be more adverse for trailing nations that are more focused on technological imitation because they must entice foreign investment by lowering tax rates (Kasadha et al, 2020;Osipov, 2017). Vatavu et al (2019) studied the effect of tax on the welfare state; surprisingly, the findings confirmed that greater taxation injects the economy with higher quality deliverance.…”
Section: Taxation and Economic Performancementioning
confidence: 99%
“…Furthermore, a study conducted by (Angelopoulos et al, 2007;Kate and Milionis, 2019) mostly contradicts previous studies on the negative effect of corporate income tax on the economy such as (Arnold et al, 2011) contend; higher corporation taxes may encourage private innovative activities and help produce funds for beneficial public investment and may promote growth while simultaneously introducing for the state some cutting edge technologies. The relationship between corporate tax rates and growth, on the other hand, may be more adverse for trailing nations that are more focused on technological imitation because they must entice foreign investment by lowering tax rates (Kasadha et al, 2020;Osipov, 2017). Vatavu et al (2019) studied the effect of tax on the welfare state; surprisingly, the findings confirmed that greater taxation injects the economy with higher quality deliverance.…”
Section: Taxation and Economic Performancementioning
confidence: 99%
“…There is scholarly need to examine the impact of media representation of female candidates in the different forms of media such as digital media (social media), radio, and television. Especially how female candidates are digitally represented in Uganda that is increasingly using social media platforms to foster political participation of youth, citizens' involvement in civic engagement related activities, and organizations digitally connecting to reconcile once conflict prone regions in Uganda (Kasadha, 2018;Kasadha, 2020aKasadha, , 2020bKasadha et al, 2020).…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…The use of digital platforms to hold a government accountable is evidenced in Rohwerder (2015) and Kasadha (2018Kasadha ( , 2020. The increased use of digital media to hold the government accountable resulted in the Ugandan government labeling them as gossip tools (AFP, 2018b) and imposed an SM tax to limit its use (Kasadha et al, 2019;Mugerwa & Malaba, 2018). However, different not-forprofit organizations in Northern Uganda shared fear over the introduced SM tax as the one that would impact citizens' willingness to engage in reconciliatory and community building discussions.…”
Section: One Of the Interviewees Observed Thatmentioning
confidence: 99%